Exposure to second-hand smoke during early life and subsequent sleep problems in children: a population-based cross-sectional study - Li-Zi Lin; Shu-Li Xu; Qi-Zhen Wu; Yang Zhou; Hui-Min Ma; Duo-Hong Chen; Peng-Xin Dong; Shi-Min Xiong; Xu-Bo Shen; Pei-En Zhou; Ru-Qing Liu; Gongbo Chen; et al. (BMC, 2021)
Abstract Background Previous studies have revealed that current secondhand smoke exposure showed highly suggestive evidence for increased risk of simultaneous sleep problems in children. Data on the associations between early-life exposure to SHS with subsequent sleep problems in children were scarce. We aimed to evaluate the associations of early-life SHS exposure with sleep problems in children. Methods In this cross-sectional study, children were recruited from elementary and middle schools in Liaoning Province, China between April 2012 and January 2013. We assessed early-life SHS exposure (pregnancy and the first 2 years of life) via questionnaires. Sleep problems and different types of sleep-related symptoms were measured based on the validated tool of the Sleep Disturbance Scale for Children (SDSC). Generalized linear mixed models were applied to estimate the associations of early-life SHS exposure with sleep problems. Results We included a total of 45,562 children (22,657 [49.7%] males; mean [SD] age, 11.0 [2.6] years) and 6167 of them (13.5%) were exposed to early-life SHS during both pregnancy and the first 2 years of life. Compared with unexposed counterparts, children exposed to early-life SHS had higher total T-scores of SDSC (β = 4.32; 95%CI: 4.06, 4.58) and higher odds of increased sleep problems (OR = 2.14; 95%CI: 1.89, 2.42). When considering different sleep-related symptoms, the associations between early-life SHS exposure and symptom of sleep-wake transition disorders (i.e., bruxism) were the strongest in all analyses. Conclusions Early-life SHS exposure was associated with higher odds of global sleep problems and different sleep-related symptoms in children aged 6-18 years. Our findings highlight the importance to strengthen efforts to support the critical importance of maintaining a smoke-free environment especially in early life.